Two new species of the copepod Hatschekia Poche, 1902 (Siphonostomatoida: Hatschekiidae) from angelfishes (Pisces: Perciformes: Pomacanthidae) collected during the KUMEJIMA 2009 Expedition - Uyeno, Daisuke; Nagasawa, Kazuya (Zootaxa, 2012)
Two new species of Hatschekia Poche, 1902 (Siphonostomatoida: Hatschekiidae) are described based on specimenscollected during the KUMEJIMA 2009 Expedition carried out at Kumejima Island, Ryukyu Islands, an area getting strongKuroshio current influence in the East China Sea, Japan. Female Hatscekia triannuli n. sp. and female and male H.sumireyakko n. sp. were removed from Centropyge heraldi Woods & Schultz and C. venusta (Yasuda & Tominaga),respectively. The two new species shares a unique dorsal frame on the cephalothorax that is absent on other congeners. These two species can be differentiated from each other by the shape and proportion of the cephalothorax, trunk, and leg 2.